A Multi-Strain Probiotic Formulation Improves Intestinal Barrier Function by the Modulation of Tight and Adherent Junction Proteins - Raffaella di Vito; Carmela Conte; Giovanna Traina (Cells, 2022)
In healthy individuals, tight junction proteins (TJPs) maintain the integrity of the intestinal barrier. Dysbiosis and increased intestinal permeability are observed in several diseases, such as inflammatory bowel disease. Many studies highlight the role of probiotics in preventing intestinal barrier dysfunction. The present study aims to investigate the effects of a commercially available probiotic formulation of L. rhamnosus LR 32, B. lactis BL 04, and B. longum BB 536 (Serobioma, Bromatech s.r.l., Milan, Italy) on TJPs and the integrity of the intestinal epithelial barrier, and the ability of this formulation to prevent lipopolysaccharide-induced, inflammation-associated damage. An in vitro model of the intestinal barrier was developed using a Caco-2 cell monolayer. The mRNA expression levels of the TJ genes were analyzed using real-time PCR. Changes in the amounts of proteins were assessed with Western blotting. The effect of Serobioma on the intestinal epithelial barrier function was assessed using transepithelial electrical resistance (TEER) measurements. The probiotic formulation tested in this study modulates the expression of TJPs and prevents inflammatory damage. Our findings provide new insights into the mechanisms by which probiotics are able to prevent damage to the gut epithelial barrier.